Determining structure of petroleum polymer resins obtained on the basis of high-boiling fractions of pyrolysis liquid products; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 3 - Bondaletova L. I. Lyudmila Ivanovna; Bondaletov V. G. Vladimir Grigoryevich; Verevkina O. V.; Manankova A. A. Anna Anatolievna (Chemistry, 2007)
Заглавие с титульного листа